Pengaruh Perilaku Helm, Kondisi Kendaraan, dan Disiplin Lalu Lintas terhadap Keselamatan Berkendara - Humaniko Silangit; Adenanthera L Dewa; Wasi Sumarsono (Logistics and Supply Chain Insights, 2025)
The main objective of this research is to analyze the simultaneous and partial influence of helmet use behavior, vehicle condition, and traffic discipline on driving safety levels on the Pandanaran Road Section, Boyolali Regency. High motorcycle usage in Indonesia contributes significantly to high accident rates, where human, vehicle, and regulatory factors are crucial elements that need in-depth assessment. The study employs a quantitative approach with a survey method, involving 100 motorcycle riders crossing the road using the Incidental Sampling technique. Data was analyzed using Multiple Linear Regression. The results indicate that all three independent variables (helmet use behavior, vehicle condition, and traffic discipline) have a positive and significant influence on driving safety. The vehicle condition variable was identified as the most dominant factor affecting driving safety, with a regression coefficient of 0.397. Overall, these three variables contribute 47.4% to driving safety. The implication of this finding emphasizes the importance of policy intervention that focuses not only on behavior but also on the supervision of vehicle technical roadworthiness.